INFLUENCE OF HYDROMORPHIE TRANSFORMATION PROCESSES ON MIKROAGGREGATE AND GRANULEMETRICAL COMPOSITION OF LOESS BREEDS - KORNIEIENKO, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On the basis of results received during performance of special complex researches of basic sites of development sink morpfosculptures in territory of region North-West seaboard Black Sea Are a new finding about composition and engineering-geological properties of a degree of loam and degradation breeds in the contours of saucers in comparison with containing loess cover. Receipt the results can be used for prognostication of change of properties of loess breeds at of long duration irrigation of territories.